Leksikon Perikanan di Kecamatan Mersam: Kajian Semantik - Rahadatul Aisy; Ernanda Ernanda; Anggi Triandana (Kajian Linguistik dan Sastra, 2023)
Abstract This study aims to determine the lexicon form of fishing gear, catch, and means of transportation, and find out the lexical meaning of fisheries in Mersam District. This research uses a qualitative descriptive research method. The data collection techniques in this study were observation, interview, recording, and write, the data that gets in the form of words. Furthermore, the data that has been obtained will be analyzed using analytical techniques, namely by transcribing data, identifying, classifying, interpreting, and drawing conclusions. "Based on the results of the analysis it can be concluded that the form of the lexicon and the lexical meaning in fisheries in the Mersam District, there are two forms of lingual units in the form of words and phrases. (1) the form of lingual units in the form of words, namely: (a) monomorphemic words in the noun category which include fishing gear as many as 22 fishing gear, such as kutik, suo, luka, serkap, pangilar, tengalak, jalo, trawl, paril, longline, kaluntang tagang, comb, tangkul, ceraah, kapucung, kelong, lapun, ranan. The lexicon consists of 41 catches such as tilan, lais, tin, sting, lalida, tatali, tapah, joro, fruit, catfish, baung, dakso, balido, dalung, sitam, semuruk, pari, saluan, etc. The lexicon consists of 3 means of transportation such as boat, boat, and raft. (2) the form of lingual units in the form of phrases, namely: (a) endocentric phrases in the noun category as many as 5 endocentric phrases in the noun category, namely, eggplant sepat, white head, green fish, durian look, and sengirik boyo." Abstrak Penelitian ini bertujuan untuk mengetahui bentuk leksikon alat tangkap, hasil tangkapan, dan alat angkut, serta mengetahui makna leksikal perikanan di Kecamatan Mersam. Penelitian ini menggunakan metode penelitian deskriptif kualitatif. Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara, pencatatan, dan tulis, data yang diperoleh berupa kata-kata. Selanjutnya data yang telah diperoleh akan dianalisis dengan menggunakan teknik analisis yaitu dengan mentranskrip data, mengidentifikasi, mengklasifikasikan, menafsirkan, dan menarik kesimpulan. Berdasarkan hasil analisis dapat disimpulkan bahwa bentuk leksikon dan makna leksikal dalam perikanan di Kecamatan Mersam terdapat dua bentuk satuan lingual berupa kata dan frasa. satuan lingual yang berupa kata, yaitu: (a) kata monomorfemik kategori nomina yang meliputi alat tangkap ikan sebanyak 22 alat tangkap, seperti kutik, suo, luka, serkap, pangilar, tengalak, jalo, pukat, paril, rawai, kaluntang tagang, sisir, tangkul, cerah, kapucung, kelong, lapun, ranan.Leksikon terdiri dari 41 tangkapan seperti tilan, lais, timah, sengat, lalida, tatali, tapah, joro, buah, lele, baung, dakso , balido, dalung, sitam, semuruk, pari, saluan, dan lain-lain.Leksikonnya terdiri dari 3 alat transportasi seperti perahu, perahu, dan rakit.(2) bentuk satuan lingual berupa frasa, yaitu: (a ) frase endosentris kategori nomina sebanyak 5 frase endosentris kategori nomina yaitu terong sepat, kepala putih, ikan hijau, durian tampang, dan sengirik boyo.â€